2022
DOI: 10.1021/acs.energyfuels.1c03747
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Additives as Flow Improvers for Waxy Crude Oil and Model Oil: A Critical Review Analyzing Structure–Efficacy Relationships

Abstract: Waxy crude oil has become a crucial unconventional oil alternative owing to the depleting conventional oil resources. However, ascertaining flow assurance in a waxy crude oil pipeline at low temperatures is challenging due to the high viscosity and gelation properties of waxy crude oil and wax deposition on the pipeline wall. Researchers and industries use different classes of chemical additives to resolve the flow assurance issues. The current review aims to build a relationship between the structural propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 151 publications
0
34
0
Order By: Relevance
“…Consequently, a higher yield stress is measured , (Figure ). While with the addition of the EVA or NPPD, the nucleation, growth, and aggregation of paraffin wax crystal grains would be modified. …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, a higher yield stress is measured , (Figure ). While with the addition of the EVA or NPPD, the nucleation, growth, and aggregation of paraffin wax crystal grains would be modified. …”
Section: Results and Discussionmentioning
confidence: 99%
“…Despite their short history, NPPDs are found to bring breakthrough in modification of paraffin wax crystallization and has therefrom attracted scholars’ great interests due to their high efficiency and low cost. ,, The main components of an NPPD are nanoparticles which possess a large specific surface area and excellent physicochemical properties . It is reported that when grafted with different polymers on its surface, the NPPD exhibits good dispersion, shear resistance, and thermal stability. An extensive body of literature exists on the synthesis of NPPDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding polymeric pour point depressants to waxy crude oil and chemically modifying it for transportation is an effective technology to improve the economics and safety of pipeline transmission. , In the process of temperature drop with pipeline transmission, polymer pour point depressants can improve the morphology, size, and aggregation state of wax crystals precipitated from waxy crude oil at low temperature, inhibit the tendency of wax crystals to form spatial network structure, and weaken the strength of wax crystals to form spatial network structure, that is, change the microscopic rheological structure of waxy crude oil at low temperature by some specific physicochemical interactions with relevant components of waxy crude oil. From the macroscopic point of view, polymer pour point depressants can reduce the pour point, viscosity, and yield stress below the WAT of waxy crude oil and weaken its complex rheological response such as viscoelasticity and thixotropy, that is, improve the macroscopic rheological properties of waxy crude oil.…”
Section: Strategies For Improving the Flowability Of Waxy Oilsmentioning
confidence: 99%
“…In recent years, the chemical viscosity reduction and cold production technology of heavy oil with low cost, low energy consumption, and low emission has become a research hotspot. , The basic principle of this technology is to make the viscosity reducer contact the heavy oil in the process of formation seepage, where self-diffusion occurs under quasi-static conditions to form emulsions, thereby reducing the viscosity of heavy oil and enhancing oil recovery. To significantly reduce the viscosity of heavy oil and simplify the implementation method, water-soluble viscosity reducers are usually used to form O/W emulsions . The successful implementation of the chemical viscosity reduction and cold production technology mainly depends on the performance of the viscosity reducer. Due to the complex structure and large difference in properties of heavy oil components, the viscosity reducer is not universal. , Therefore, the use of appropriate methods to accurately determine the self-diffusion performance of viscosity reducers plays a vital role in their optimization.…”
Section: Introductionmentioning
confidence: 99%